Presentation of cerebral and cervical arterial dissections in botucatu, brazil: Case series - Modolo, Gabriel Pinheiro [UNESP] (2021)
Spontaneous dissection of the cervical and cerebral arteries is an important cause of stroke and disability in young patients. In this report, the authors present a case series of patients with spontaneous carotid, vertebral, or cerebral artery dissection who underwent digital angiography. A review of the published literature on this subject is also presented.